Perencanaan Struktur Apartemen 5 Lantai +1 Basement Dengan Sistem Rangka Pemikul Momen Menengah (SRPMM) Di Sukoharjo - Hanafi, Muhammad Burhanudin; , Ir. Abdul Rochman, M.T; , Budi Setiawan, ST, MT (2015)
Sukoharjo is a town that is going rapidly in aspect of business or in infrastructure makes need of housing more. There for, it will be planned an apartment with 5 floors + 1 basement with Intermediate Reinforced Concrete Moment Resisiting Frames (I-MRF) in that area. The structure which is planned must be in safe aspect, architectural and economical. The planning has reference with Indonesia Standard Regulation (SNI) that has been established, namely SNI-1726:2012 (the rules of building structure earthquake for building structure and non-structure) and SNI-2847:2013 (requirenment of concrete structural for building structure). This plan includes the main structure (superstructure and substructure) and non-structural components (roof structure, plate structure, stairs and basement retaining wall). With the building location in Sukoharjo (latitude -7,558 longitude 110,772) and soil site clasification is SD (intermediate soil), so it gets value SDS and SD1 is 0,579g and 0,324g. For designing of earthquake building with I-MRF, it's used value for the importance factor Ie 1,0 (housing, risk category II), response modification factor (R) is 5, deflection amplification factor (Cd) 4,5 and overstrength factor (Ω0) is 3. Concrete quality is fc' 25 MPa, with steel reinforcement fy 400 MPa and 250 MPa. Beam structure is planned with dimention 350/700 for the first and second storey, 300/650 for the third storey to fifth 300/500 for the roof story. Whereas column is planned with dimention 600/700 for basement to the second storey and 550/600 for the third until the fifth storey. The substructure is planned using pile foundation with pile cap 3x3 m and pile depth 16 m with dimention 40x40 cm.